Creation of an inventory of skills for the teaching of literacy in the first and second grades of primary school. (REVISTA CIENTÍFICA SIGNOS FÓNICOS, 2020)
INTRODUCTION: During the early stage of language development, you learn skills that are important for the development of literacy. METHODS:This study is a quantitative non-experimental cross-sectional design developed in a public institution in the municipality of Villa del Rosario during the second period of 2019. RESULTS:the variables organization, reading, writing and reading-writing arethe main axes for the comparison between the basic learning rights governed by the ministry of national education and the practical task of the teacher.ANALYSIS AND DISCUSSION:The infant is a social being since birth is related to the surrounding environment, handling different forms of communication, such as crying, words.CONCLUSIONS: The 4 offices carry out the management of the ICTs, taking into account the DBA, the readingand writing components are the most used since these are fundamental for the development of other areas.
Keywords: writing; reading; children; education; teacher